Respuestas

  • Usuario de Brainly
2014-01-15T04:04:21+01:00
Solución:
6x^2 + 13x - 5 =0
Fórmula
=> x = [ -13 +- V{(13^2) - (4)(6)(-5)}] / (2(6))

=> x = [ -13 +- V( 169 + 120) ] / 12

=> x = [ -13 +- V( 289) ] / 12

=> x = [ -13 +- 17 ] / 12

=> x(1) = [ -13 + 17] / 12 => x(1) = 4/12 => x(1) = 1/3 ....Rta.

=> x(2) = [ -13 - 17] / 12 => x(2) = -30/12 => x(2) = -5/2 .... RTa.

2) 5y^2 - 3 = 0

=> 5y^2 = 3
=> y^2 = 3/5
.................____
=> y =+- V( 3/5)  ..... Rta.

3) x^2 - 6x + 2 = 0

=> x^2 - 6x + (6/2)^2 = -2 + (6/2)^2

=> x^2 - 6x + (3)^2 = - 2 + (3)^2

=> x^2 - 6x + 9 = -2 + 9

=> x^2 - 6x + 9 = 7

=> (x - 3) ^2 = 7
....................__
=> x-3 = +- V(7)
.....................___
=> x = 3 + - V(7) 
......................___
=> x(1) = 3 + V(7) .... Rta.
.....................___
=> x(2) = 3 - V(7) .... Rta.
suerte.